Pengaruh Latihan Ladder Drills dan Latihan Small Sided Games Terhadap Prestasi Keterampilan Menggiring Bola di SSB Putra Mandiri - Setyawan, Bangkit; Hudah, Maftukhin; Pradipta, Galih Dwi (Pena Edukasia, 2023)
The author's research method is a quantitative method. This research design is a pretest design with one-group-pretest and posttest-design. The population for research was only SSB Putra Mandiri students, totaling 36 students. The sample was taken using a non-probability sampling method, namely SSB Putra Mandiri, 20 students aged 10 to 15 years. This research data was obtained through student learning outcomes. The data analysis method uses the t-test. The following results show that based on the pre-test data from the ladder training exercise, the max value is 29, the min value is 20 and the average value is 29,24,95. Meanwhile, the results of the stair training after the test obtained a max value of 31, a min value of 23, and an average value of 27.7. Based on these results, the number of athletes increased by 27.5%. Based on the small group game practice pretest data above, a max score of 8, min score of 2, and average score of 5.15 were obtained. Meanwhile, the training results after the small group game had a max score of 9, min score of 2 and an average score of 5.90. Based on these results, the athlete received 7.5%. The suggestion that researchers can convey is for teachers to be more creative in using media so that students are more intereste.